Down-regulation of CD55 and CD46 expression by anti-sense phosphorothioate oligonucleotides (S-ODNs) sensitizes tumour cells to complement attack - Zell, S (Blackwell Science Inc, 2007)
Overexpression of one or more membrane-bound complement regulatory proteins (mCRPs) protects tumour cells against complement-mediated clearance by the autologous humoral immune response and is also considered as a barrier for successful immunotherapy with monoclonal anti-tumour antibodies. Neutralization of mCRPs by blocking antibodies, enzymatic removal or cytokine-mediated down-regulation has been shown to sensitize tumour cells to complement attack. In our study we applied, for the first time, anti-sense phosphorothioate oligonucleotides (S-ODNs) to knock down the expression of the mCRPs CD55 and CD46 with the aim of exploiting complement more effectively for tumour cell damage. Potent anti-sense oligonucleotides against CD55 and CD46 were identified by screening various target sequences (n = 10) for each regulator. S-ODN anti-CD55(687) reduced CD55 protein expression up to 84% and CD46 protein expression was inhibited up to 76% by S-ODN anti-CD46(85). Reverse transcription–polymerase chain reaction (RT–PCR) analysis revealed a similar reduction of the CD55 and CD46 mRNA levels, which argues for an RNAse H-dependent anti-sense mechanism. T47D, A549 and PC3 cells, representing breast, lung and prostate carcinoma, were used for functional studies. Dependent on the particular cell line, anti-sense-based inhibition of mCRP expression enhanced complement-dependent cytolysis (CDC) up to 42% for CD55 and up to 40% for CD46, and the combined inhibition of both regulators yielded further additive effects in T47D cells. C3 opsonization of CD55/CD46-deficient tumour cells was also clearly enhanced upon mCRP suppression. Due to the clinical applicability of S-ODNs, the anti-sense approach described in this study may offer an additional alternative to improve the efficacy of antibody- and complement-based cancer immunotherapy.